KAJIAN PENERAPAN ASAS ULTRA PETITA PADA PETITUM EX AEQUO ET BONO - Bambang Sugeng Ariadi Subagyono; Johan Wahyudi; Razky Akbar (Universitas Airlangga, 2014)
In judicial practice, that more than likely a lawsuit granted by the court , it often demands the principal ( the primary petition ) is accompanied by replacement demand ( petitum subsidiary ). The contents of the demands it usually reads :